Self Compacting Concrete Shear Walls using Solid65 Element (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The main objective of this paper is to study the structural behavior of self-compacting concrete shear wall. The study an analysis of two SCC shear walls has been conducted to the tested specimens by using a three dimensional nonlinear finite element method by ANSYS software.In the present work is able to simulate the behavior of SCC shear walls without openings. The numerical ultimate loads are slightly lesser than those obtained from experimental work. The ratio of numerical ultimate load to experimental ultimate load is between 0.9 and 0.99. The adopted finite element analysis showed a good agreement with experimental results. The crack patterns obtained from the finite element models are comparable with the crack patterns observed in the experimental work and was very well in agreement.